Wage inequality and structural change - Foundation of Admirers and Mavens of Economics, Warsaw; Smyk, Magdalena; Tyrowicz, Joanna (Warsaw, 2017)
"Income inequality in the context of large structural change has received a lot of attention in the literature, but most studies relied on household post-transfer inequality measures. This study utilizes a novel and fairly comprehensive collection of micro datasets between 1980s and 2010 for both advanced market economies and economies undergoing transition from central planning to market based system. We show that earned income inequality was initially lower in transition economies and immediately upon the change of the economic system surpassed the levels observed in advanced economies. We decompose changes in wage inequality into parts that can be attributed to changes in characteristics (mainly education) and changes in rewards, but did not find any leading factor. Finally, in the context of skill-biased technological change literature we find a very weak link between structural changes and wages in both advanced and post-transition economies. %This holds regardless of whether an economy has underwent a large structural shock or not."